1996
DOI: 10.1002/j.1460-2075.1996.tb00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Bni1p implicated in cytoskeletal control is a putative target of Rho1p small GTP binding protein in Saccharomyces cerevisiae.

Abstract: The RHO1 gene encodes a homolog of mammalian RhoA small GTP binding protein in the yeast Saccharomyces cerevisiae. Rho1p is localized at the growth sites, including the bud tip and the cytokinesis site, and is required for bud formation. We have recently shown that Pkc1p, a yeast homolog of mammalian protein kinase C, and glucan synthase are targets of Rho1p. Using the two‐hybrid screening system, we cloned a gene encoding a protein which interacted with the GTP‐bound form of Rho1p. This gene was identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
240
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(249 citation statements)
references
References 52 publications
7
240
2
Order By: Relevance
“…The interaction of TC10 with pro®lin may provide valuable insights into mechanisms linking cytoskeletal rearrangements to the Rho family. For example, the recent observations that budding yeast Cdc42p and Rho1p, required for actin cytoskeletal reorganization during bud site initiation and growth, respectively, bind to Bni1p and that Bni1p is itself a pro®lin-binding protein that participates in cell polarization (Kohno et al, 1996;Evangelista et al, 1997), suggest both that additional links may exist and that pro®lin may play a key role in all of them. We expect that a biochemical and functional characterization of the TC10 GTPase and its interactions with pro®lin may provide insight into general features of the links that couple Rho family GTPases to the cellular state of the actin cytoskeleton and to the processes that control cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of TC10 with pro®lin may provide valuable insights into mechanisms linking cytoskeletal rearrangements to the Rho family. For example, the recent observations that budding yeast Cdc42p and Rho1p, required for actin cytoskeletal reorganization during bud site initiation and growth, respectively, bind to Bni1p and that Bni1p is itself a pro®lin-binding protein that participates in cell polarization (Kohno et al, 1996;Evangelista et al, 1997), suggest both that additional links may exist and that pro®lin may play a key role in all of them. We expect that a biochemical and functional characterization of the TC10 GTPase and its interactions with pro®lin may provide insight into general features of the links that couple Rho family GTPases to the cellular state of the actin cytoskeleton and to the processes that control cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…The FH1 region is a proline-rich stretch that recruits profilin, an actin-monomer binding protein essential for formin function in vivo , to participate in FH2-mediated nucleation in vitro (Sagot et al, 2002b;Kovar et al, 2003;Pring et al, 2003). Other regions present in Bni1p and Bnr1p are a regulatory NH 2 -terminal rho-GTPase-binding domain that subjects many formins to rho-dependent activation (Kohno et al, 1996;Evangelista et al, 1997;Imamura et al, 1997;Dong et al, 2003), and an FH3 motif that helps localize formins within the cell (Petersen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The FH1 region is a proline-rich stretch that recruits profilin, an actin-monomer binding protein essential for formin function in vivo , to participate in FH2-mediated nucleation in vitro (Sagot et al, 2002b;Kovar et al, 2003;Pring et al, 2003). Other regions present in Bni1p and Bnr1p are a regulatory NH 2 -terminal rho-GTPase-binding domain that subjects many formins to rho-dependent activation (Kohno et al, 1996;Evangelista et al, 1997;Imamura et al, 1997;Dong et al, 2003), and an FH3 motif that helps localize formins within the cell (Petersen et al, 1998).With loss of formin function, actin cables disassemble in 2 min, and a cytokinetic ring is unable to assemble, but actin patches remain intact Sagot et al, 2002a;Tolliday et al, 2002). Other actin nucleators, particularly the Arp2/3 complex, play no apparent role in cable or cytokinetic ring assembly in budding yeast (Winter et al, 1999;Evangelista et al, 2002;Tolliday et al, 2002), suggesting the formins might be in vivo nucleators for these actin filaments.…”
mentioning
confidence: 99%
“…Rho1p regulates the reorganization of the actin cytoskeleton at least through the Bni1p-pro®lin system in the budding yeast (Kohno et al, 1996;Imamura et al, 1997). We have examined a possible interaction of ABP140 with Rho1p, Bni1p, and pro®lin by use of the yeast two-hybrid system.…”
Section: Discussionmentioning
confidence: 99%
“…RHO1 is a counterpart of the mammalian RhoA gene and we have shown that the rho1 mutants are de®cient in the budding process . We have recently identi®ed the downstream targets of Rho1p to be Pkc1p, 1,3-b-glucan synthase, and Bni1p (Nonaka et al, 1995;Drgonova et al, 1996;Kohno et al, 1996). Pkc1p is a homolog of mammalian protein kinase C and regulates cell wall integrity through activation of the MAP kinase cascade (Levin and Errede, 1995).…”
Section: Introductionmentioning
confidence: 99%